ESTUDO DA GERMINAÇÃO DE Delonix regia RAF (Poinciana regia BOJER) (LEGUMINOSAE) - Pagotto, T. C. S.; Schlittler, F. H. M.; Marin, M. A.; Piccolo, A. L. G. (REVISTA DE AGRICULTURA, 2015)
ESTUDO DA GERMINAÇÃO DE Delonix regia RAF (Poinciana regia BOJER) (LEGUMINOSAE)